Climate change and the health profession in South Africa - Bob Mash (South African Family Practice)
Climate change is arguably the most important public health issue of the next decade. The impact of climate change should be understood in the broader context of population growth, degradation of ecosystems, inequality, food insecurity, urbanisation, slums and peak oil. Climate change is the result of deforestation and excess greenhouse gases from the burning of fossil fuels. Environmental consequences include rising global temperatures, melting of sea ice and glaciers, rising sea levels, flooding, more frequent and severe storms and changes in climatic patterns. Medical consequences stem from extreme climatic events, changes in the patterns of infectious diseases, increased food insecurity, displacement of populations, lack of fresh water and conflict over resources. South Africa has a relatively high carbon footprint. The health profession should respond as opinion leaders, as professional bodies and as an industry.